(untitled) (Central Asian Journal of Medical Sciences, 2016)
Objectives: Chronic neutrophilic leukemia (CNL) is a rare, but distinct, entity within myeloproliferative neoplasms, characterized by splenomegaly, sustained mature neutrophilia, and absence of the Philadelphia chromosome. In 2013, oncogenic mutations in colony stimulation factor 3 receptor (CSF3R) were identified in a majority of patients with CNL and it was demonstrated that their downstream signaling was sensitive to known kinase inhibitors. This discovery was then validated with the demonstration of 100% CSF3R mutational frequency (predominately CSF3R-T618I) in strictly CNL as defined by the World Health Organization (WHO). In September 2012, a 67-year-old Chinese man was admitted to the First Central Clinical College of Tianjin Medical University (Tianjin, China) and presented as a case who had fulfilled the WHO diagnostic criteria for CNL with a oncogenic mutation in CSF3R-T618I and also an unreported novel mutation site of CSF3R-H54A Thus, we sought to determine if CSF3R-FL, CSF3R-T618I, CSF3R-H54A mutations have some significance on the molecular pathogenesis of CNL. Methods: In this study, three main experiments were used including plasmid construction, lentiviral packaging system, and Mouse Colony-Forming Unit Assays Using MethoCult™. Results: The establishment of these three experiments was completed successfully. We confirmed the transformation capacity of the CSF3R mutations, especially that CSF3R-T618I was higher than CSF3R-FL Conclusion: This result demonstrates that T618I mutation of CSF3R conferred the clonal advantage of CNL leukemia cells.